PALEOBIOGEOGRAPHY AND PALEOECOLOGY OF THE OSTRACOD HELIOCYTHERE BONADUCE, RUGGIERI & RUSSO, 1988 WITH RE-DESCRIPTION OF MIDDLE MIOCENE HELIOCYTHERE MORAVICA (PROCHÁZKA, 1893) FROM THE CARPATHIAN FOREDEEP (CZECH REPUBLIC) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2015)
Twelve species attributed to the genus Heliocythere have been recorded from the epineritic/neritic and circalittoral/epibathyal deposits of Cenozoic subtropical seas. The oldest species is from the Lower Oligocene deposits of the northwest Indian Ocean. The youngest species are confirmed from the Late Miocene (Messinian) of the Mediterranean area and one stratigraphically uncertain record from the Early Pliocene of Vejer de la Frontera (southern Spain). Heliocythere profited of a marine connection between the Mediterranean and the Paratethys through the Slovenian corridor during the latest Burdigalian (Karpatian) and settled in Central Europe and Balkan Peninsula marine biotopes, but a paleogeographic and paleoecologic change during the late Serravallian caused an extinction of Paratethyan Heliocythere . In Late Miocene times, Heliocythere spread through the entire Mediterranean area and extended its biogeographic range to the eastern Atlantic Ocean. This was a period of maximum species diversity of Heliocythere. No Heliocythere species has been described from present-day marine ostracod associations and we suppose that this fully marine genus is extinct.Due to the loss of the type material and the necessary correction of genus attribution, we designate herewith a neotype for theearly Badenian (early Langhian) Cythere moravica Proch√°zka, 1893 from the Carpathian Foredeep, referred to in this work as Heliocythere moravica (Proch√°zka, 1893). We discuss its paleoecology and position within the genus Heliocythere .